Study the Relationship Between Vit.D and Some Biomarkers in Female Hair Loss Patients Compared to Normal Subjects - Hajem, Nashaat S.; Matok, Majid A.; Ali, Dawood S. (American Journal of Biology and Natural Sciences, 2025)
Background: Female Pattern Hair Loss (FPHL) is a common non-scarring form of alopecia among women, often associated with psychosocial distress. Although its exact pathophysiology remains unclear, recent research highlights potential roles of micronutrients, neurotransmitters, and metabolic factors, such as vitamin D, dopamine, and lipid profiles. Methodology: A case-control study was conducted from December 2024 to March 2025 at Al-Qurna General Hospital and Al-Faihaa Teaching Hospital in Basra, Iraq, involving 65 female FPHL patients and 65 healthy age-matched controls. Participants underwent clinical evaluation and blood sampling to assess serum levels of dopamine, vitamin D, ferritin, and lipid profile components using ELISA and Cobas e411. Statistical analyses were performed using SPSS v26 with significance set at p ≤ 0.05. Results: The study found significantly lower serum levels of vitamin D and ferritin in FPHL patients compared to controls (p < 0.001). Dopamine levels showed no significant difference between groups (p = 0.34). Lipid profile analysis revealed significantly lower total cholesterol and triglyceride levels in patients (p = 0.03 and p < 0.001, respectively), with no significant changes in HDL, LDL, or VLDL levels. Subgroup analysis by age within the patient group indicated age-related variations in lipid parameters but not in vitamin D or dopamine levels. Conclusion: The findings suggest that vitamin D deficiency and altered lipid metabolism may play significant roles in the pathogenesis of FPHL, while serum dopamine appears not to be directly implicated. These results support the potential benefit of monitoring vitamin D and lipid status in women with FPHL and highlight the need for further investigation into metabolic contributors to this condition.